CoCl2, a mimic of hypoxia, enhances bone marrow mesenchymal stem cells migration and osteogenic differentiation via STAT3 signaling pathway. (2nd July 2018) - Yu, Xin; Wan, Qilong; Cheng, Gu; Cheng, Xin; Zhang, Jing; Pathak, Janak L.; Li, Zubing
Abstract: Mesenchymal stem cells homing and migration is a crucial step during bone fracture healing. Hypoxic environment in fracture site induces bone marrow mesenchymal stem cells (BMSCs) migration, but its mechanism remains unclear. Our previous study and studies by other groups have reported the involvement of signal transducer and activator of transcription 3 (STAT3) pathway in cell migration. However, the role of STAT3 pathway in hypoxia‐induced cell migration is still unknown. In this study, we investigated the role of STAT3 signaling in hypoxia‐induced BMSCs migration and osteogenic differentiation. BMSCs isolated from C57BL/6 male mice were cultured in the presence of cobalt chloride (CoCl2 ) to simulate intracellular hypoxia. Hypoxia enhanced BMSCs migration, and upregulated cell migration related gene expression, that is, metalloproteinase ( MMP ) 7, MMP9, and C‐X‐C motif chemokine receptor 4. Hypoxia enhanced the phosphorylation of STAT3, and cell migration related proteins: c‐jun n‐terminal kinase (JNK), focal of adhesion kinase (FAK), extracellular regulated protein kinases, and protein kinase B 1/2 (ERK1/2). Moreover, hypoxia enhanced expression of osteogenic differentiation marker. Inhibition of STAT3 suppressed the hypoxia‐induced BMSCs migration, cell migration related signaling molecules phosphorylation, and osteogenic differentiation related gene expression. In conclusion, our result indicates that hypoxia‐induced BMSCs migration and osteogenic differentiation is via STAT3 phosphorylation and involves the cooperative activity of the JNK, FAK, and MMP9 signaling pathways.